Investigation of SAR-associated small molecules as inducers of resistance in cucumber and biofilm formation by Pseudomonas syringae pv. tomato in Arabidopsis - Fufeng, Angela B. (My University, 2019)
Greenhouse environments often promote bacterial and fungal infections in important crop plants. Exogenous application of chemical inducers could help reduce the severity of infection, or even prevent infection. Small molecules such as glycerol, azelaic acid and pipecolic acid have been implicated as being important signaling molecules during Systemic Acquired Resistance (SAR). To examine if these small molecules could be used to induce resistance in crop plants, exogenous treatment assays were developed in cucumber. Glycerol spray and azelaic acid infiltration induced modest resistance at locally treated leaves. Pipecolic acid soil treatment induced modest resistance in aerial tissue of cucumber plants, and strong resistance when plants were treated weekly. This knowledge may be useful in promoting the commercialization of SAR-associated compounds to protect important crop plants against disease. Plants possess multiple defense pathways that include an SA signaling component to initiate resistance to microbial pathogens. However, during Age-Related Resistance (ARR) in Arabidopsis, a number of studies support that SA acts as an anti-microbial and anti-biofilm agent against Pseudomonas syringae pv. tomato (Pst) in the plant intercellular space. Little is known about the role of Pst biofilm formation during infection of young plants or if other defense responses act to suppress bacterial biofilm formation. Therefore Pst biofilm formation and the effect of PAMP Triggered Immunity (PTI) on bacterial biofilm formation was examined. PTI was induced with flg22 in wild-type Col-0, fls2, bak1-3 (PTI mutants) and sid2-2 (SA biosynthesis mutant). In vivo bacterial biofilm-like aggregate formation was monitored using Pst DC3000 PDSK-GFPuv and epifluorescence microscopy. Pst aggregate occurrence and size were positively correlated with bacterial success in susceptible plants (wild-type Col-0, fls2, bak1-3, sid2-2), while fewer and smaller bacterial aggregates were observed in Col-0 undergoing PTI. To determine if the extracellular polysaccharide, alginate was a major contributor to biofilm formation, in vivo bacterial aggregate formation was monitored using alginate deficient Pst-GFP. Alginate deficient Pst-GFP and wild-type Pst grew to similar levels in wild-type plants suggesting that the ability to produce alginate was not necessary for Pst pathogenicity and success in planta. Fewer alginate-deficient Pst aggregates were observed compared to wild-type Pst in inoculated plants, suggesting that the ability to produce alginate was modestly important for aggregate formation. These data provide novel insights into how biofilms form in planta, the association between pathogen virulence and biofilm formation, and how plant defense responses such as PTI not only reduce bacterial growth, but also target biofilms.
Keywords: Pseudomonas syringae; Biofilm; Cucumber; Arabidopsis; Systemic Acquired Resistance; PAMP-triggered immunity